An Expert`s Oponion on the 1999 Women`s Youth Europen Championship in GER - Leukefeld, D.; Pollany, W.; Taborsky, F (coachesinfo.com)
Leukefeld: The German Women`s Youth National Team (DHB selection) has played 40 international matches in order to prepare for the 1999 Women`s Youth European Championship in GER. 150 players were tested in a three and a half year period. One third of the team was selected in regional training courses that took place beforethis period. Due to the different performance level of the players at the beginning of preparations the tactical training focused on the improvement of individual tactical skills for a two year period. At the same time emphasis was put on the psychological and mental development of the players. It was our objective to focus on the players` personalities, to improve both their creativity and self-confidence. Only in a few regional federations ( e.g.: Baden Würtemberg and Sachsen-Anhalt ) the concept was followed that it had to be the best coaches that should work with our young national team players, at least that they should be involved regularly in regional courses. The biggest problem turned out to be the different hours of training sessions each of our players were used to. Members of handball sport schools or 1st division ( Bundesliga ) players practise 6-8 times a week, whereas 2nd division or 3rd division ( Regionalliga ) players only 3 times. The most important experience from this ECh is that in the years to come only those players shall be selected who have the chance to practise every day. Currently together with all coaches involved I am checking the requirements for putting this concept into practice. In Germany we have created good pre-conditions for the implementation of a uniform training concept by using the framework training concept of our federation as well as the general concept for developing top level sport. The problem we have is the fact that these concept are not transparent, well-known enough to reach the coaches and consequently the players at the basis. Unfortunately some of the coaches in youth handball are still not very well educated, mainly concerning their competence of using the adequate concepts for the right age group of players or leadership abilities. Let me now try to evaluate the ECh final round group, GER had to play in. In my opinion this group was much stronger than the other, mainly because of DEN, NOR, RUS, CRO and CZE having both excellent players in this age group and much experience in European youth handball. However, we reached the semi-final, where we have to play ROM. We will have a chance, if we speed up the game in order to compensate physical deficiencies and our goalies perform very well. Pollany: Picking up the statement of Leukefeld, Pollany added that the situation in Austria was even more difficult than in Germany because female handball there has to be seen as a kind of leisure sport at all. Not more than one or two teams all over the country can claim to work on performance sport in handball all the other teams can be called by the way formations doing handball more or less by chance because of friends, relatives or somebody else close to them involved in the game before. One of the big problems is the traditional role of females in central Europe opposing a real professional performance in any kind of team sport. This situation is different in Scandinavia where women have a better position in society overall and therefore do show more self esteem and more competence in terms of sport activities in general and in team sport in particular. Another problem is the process of developing young players because most of the coaches like in male handball are aiming for fast or even instant success rather than for educating athletes on a long term planning. Therefore a lot of expat players are used in female handball as well as in male. The point is that with the lower number of female handball players and the different position of these expats coming from countries with a very big and long tradition in female handball and having a lot of advantage in any respect of the prerequisites for top level handball the situation is much worse than in male handball and the effects of a system like that are more demolishing to the perspectives of young native players. Taborsky: Before taking a closer look at the teams, let me ask the question, by way of introduction, why some nations are always successful and others - even nations with a long tradition - only rarely or never at all. This development seems to be influenced by a variety of factors. In the case of DEN and NOR, it is the high regard in which women's sports are held nationally. KOR, AUT and NED concentrate their resources on numerically small teams. ROM, RUS and FRA possess an educational structure in the form of handball schools. In CZE, handball schools were closed after the breakdown of communism; now, attempts are made to revive those schools again as one has realised that they had formed the very basis of Czech handball. In contrast to the senior women's EChs (which have been dominated for years by DEN and NOR), there is substantial fluctuation in medallists in the Women's Youth and Junior European Championships, which is certainly attributable to the qualification system and the different strengths of different birth years. But let me come to the subject proper: a brief characteristic of the teams playing in the semifinals of the 1999 Women's Youth ECh in GER. ROM: Generally very good players in all positions; good 6:0 and 5:1 defence formations; excellent 1st wave but less impressive 2nd wave in fast breaks; position attack slightly unimaginative. SWE: Very mobile 6:0 defence with a good block; very good 2nd wave in the fast break; do without the two wings in position attack (leave them standing at the goal line); make their play by good crossing moves in the back and surprising jump passes to the outsides. RUS: 5:1 defence formation with a highly mobile forward and 2 players alternating between attack and cover tasks; one clear game-maker who, apart from being the right back, is also the best thrower. A disadvantage is the lack of a left-handed player. The goalies are somewhat less effective. GER: Physically, the shortest team of all semi-finalists; 5:1 defence formation with a good forward and a very good goalie; good 1st wave in the fast break but poor 2nd wave; in position attack, attacks are extended over a long time, culminating in underarm shots, surprise shots, and breakthroughs.